Who benefits from the sanitized language of violence? - Fyjis-Walker, Matthew (Brill/Nijhoff, 2024)
"Language is not neutral; it determines, and is determined, by perspective. This volume explores the role of an influential vocabulary of war, sanitised language, the language that seeks to clean up the appearance of events through euphemism, abstract words and opaque phrases. Critical discourse analysis of the language of recent military campaigns shows that the public authorities do not explain events as clearly as they might. Despite social, political and strategic incentives to use sanitised language, its use appears to undermine the democratic process and reduce public authorities' freedoms, possibly emboldening adversaries and turning away potential partners"-- Provided by publisher.
Keywords: Military law -- Great Britain.; Military ethics -- Great Britain.; Law -- Great Britain -- Language.; Civil-military relations -- Great Britain.; War (International law); Violence (Law); Euphemism.; Great Britain -- Military policy.; Morale militaire -- Grande-Bretagne.; Droit -- Grande-Bretagne -- Langage.; Relations pouvoir civil-pouvoir militaire -- Grande-Bretagne.; Guerre (Droit international); Violence -- Droit.